004 Physical activity monitoring to assess disability progression in multiple sclerosis. Issue 6 (27th May 2022) - Stuart, Charlotte M; Philip, Sheaba; Galea, Ian; Group, SIMSStudy
Abstract : To monitor multiple sclerosis (MS) disability, scales like the Expanded Disability Status Scale (EDSS) and Multiple Sclerosis Functional Composite (MSFC) are commonly used. Both rely on a single clinical assess- ment in time which may not reflect the patient's performance in their living environment. They also require training and are time consuming. The SenseWear armband incorporates a triaxial accelerometer sensitive to upper and lower limb motion. A proprietary algorithm computes several physical activity variables, such as total energy expenditure, physical activity duration, metabolic equivalents (METs) and average daily steps. Here we assess the SenseWear armband for its ability to monitor disease progression, alongside the EDSS and MSFC. Progressive MS patients (n=50) wore the device for one week, every 6 months for 2.5 years. MSFC and EDSS were performed at the end of each week. The armband was agreeable and easy to use. Patients showed progression across all three disability measures (p<0.01). Baseline physical activity, EDSS and MSFC values correlated well between each other. The change in the three measures with time correlated poorly, suggesting that they measure functional aspects which have different pro- gression trajectories. In summary, physical activity monitoring is a user-friendly and ecological method to measure MS disability progression. c.stuart@soton.ac.uk